Clapton the autobiography - Clapton, Eric 1945- (Broadway Books, 2007)
The legendary guitarist recounts the story of his life and his career, recalling his work with the Yardbirds, Cream, and as a solo artist; years of drug and alcohol abuse; failed marriage to Patti Boyd; and the accidental death of his young son.
Keywords: Clapton, Eric; Clapton, Eric -- 1945-; Rock musicians -- England -- Biography; Autobiografie; Fiktionale Darstellung